HCMV-IE2 promotes atherosclerosis by inhibiting vascular smooth muscle cells’ pyroptosis - Ma, Guixin; Yu, Zhongjie; Nan, Fulong; Zhang, Xianjuan; Jiang, Shasha; Wang, Yunyang; Wang, Bin (Frontiers in Microbiology, 2023)
Atherosclerosis is still the main cause of death in developed and developing countries. Vascular smooth muscle cells (VSMCs) death disorder is one of the key pathogeneses of atherosclerosis. During the early stage of HCMV infection, IE2 is critical in regulating its host cell death to ensure HCMV replication. Abnormal cell death induced by HCMV infection contributes to the development of numerous diseases, including atherosclerosis. Hitherto, the underlying mechanism of HCMV involved in the progression of atherosclerosis is still unclear. In this study, the infection models in vitro and in vivo were constructed to explore the pathogenesis of HCMV-related atherosclerosis. Our results indicated that HCMV could contribute to the progression of atherosclerosis by enhancing the proliferation, invasion, and inhibiting the pyroptosis of VSMCs under inflammatory conditions. Meanwhile, IE2 played a key role in these events. Our present research revealed a novel pathogenesis of HCMV-related atherosclerosis, which might help develop new therapeutic strategies.